Interpersonal Communication Management Between School Principals and Teachers in Fostering Discipline at MTs Darussa’adah Islamic Boarding School - Novita Sari; Syarifah Hidayani; Ahmad Zaki (Education Achievement: Journal of Science and Research, 2024)
Social relationships are desired if someone feels that their self-esteem or sense of security will increase, and this relationship will be realized by carrying out harmonious communication. Interpersonal communication is a communication process that is considered the most effective and the process can be done in a very simple way. Apart from being an important element, interpersonal communication is a "bridge" in establishing social relationships between people. Apart from being effective, interpersonal communication is a communication process that is considered important and a necessity for every person, both in formal and non-formal organizations. Therefore, it is important for everyone to have communication skills, without being limited by position, social status or stratification in social life. This research uses qualitative research, with descriptive qualitative research type. The research subjects were madrasah principals and Darussa'adah Darussa'adah teachers. Data collection techniques using interviews, observation and documentation. The research results aim to find out the obstacles that teachers findDarussa'adah Darussa'adahin increasing student learning motivation in the new normal era. The research results aim to determine the planning, organization and implementation of interpersonal communication between madrasa heads and teachers in fostering teacher discipline at Darussa'adah Darussa'adah. The results of this research show that the interpersonal communication management of madrasah heads and teachers in fostering discipline, namely